Arab Republic of Egypt Student Assessment : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
The Arab Republic of Egypt has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component of efforts to improve the quality of education and learning outcomes because it provides the necessary information to meet stakeholders’ decision-making needs. To gain a better understanding of the strengths and weaknesses of its existing assessment system, Egypt decided to benchmark this system using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The key policy areas for this student assessment status for Egypt are as follows: (i) Classroom Assessment; (ii) Examinations; (iii) National Large-Scale Assessment (NLSA); and (iv) International Large-Scale Assessment (ILSA).